JURIDICAL IMPLEMENTATION OF LOSS OF CERTIFICATE OF DEPENDENCY RIGHTS IN THE ROYA PROCESS - Teguh Pribadi; Fikri Nugraha; Ulipah Ulipah; Irma Maulida (Ann Publisher, 2025)
Abstract: Background. In daily life, many people buy houses or land through credit from banks. When the certificate is used as collateral, dependent rights will be recorded on the certificate. After the debt is paid off, the landowner must delete the Dependent Rights through roya at the National Land Agency (BPN). Roya can be done after the debt guaranteed in the main agreement has been paid off. However, if the certificate of dependency rights is lost, then a Roya Consent Deed made by a notary is needed instead. Aims. This study discusses the juridical implementation of the loss of the Right of Dependency certificate in the Roya process, namely the removal of the Right of Dependency from the land book due to debt repayment by the debtor. In practice, the lost Dependent Rights certificate raises administrative problems, because the certificate is a valid written evidence in the ROYA process. However, based on the provisions of land law and technical policies of the Land Office, roya can still be implemented as long as the applicant, both creditors and debtors with the approval of the creditors, can meet formal requirements such as a loss report from the police, a statement of absolute responsibility, and proof of payment of debt obligations. Methods. This study uses a normative juridical approach with secondary data sources from laws, regulations, and land administration documents. Result. The study's results show that the Land Office can still process roya without a certificate of Dependent Rights as long as all procedures and supporting documents are met. Conclusion. This reflects applying the principles of legal certainty, protection of civil rights, and efficiency in public services in the land sector. Implementation. This reflects the law's flexibility in answering practical problems in the field while emphasizing the Land Office's active role in ensuring legal protection for all parties involved in the transfer and abolition of land rights.